Mechanistic insights into the transformation processes in Z-phase strengthened 12% Cr steels. (15th November 2018) - Rashidi, M.; Golpayegani, A.; Sheikh, S.; Guo, S.; Andrén, H.-O.; Liu, F.
Abstract: Compositionally complex Z-phase strengthened 12% Chromium steels are considered as potentially viable materials for components used in highly-demanding environments in steam power plants, operating at a target temperature of 650 °C. To date, however, the transformation processes of various phases into the desired precipitate, i.e., Z-phase CrTaN, are not fully understood. In this research, we first designed and produced three different alloys and then studied the microstructure in the as-tempered and aged conditions (for up to 10, 000 h at 650 °C) using advanced electron microscopy, X-ray diffraction, and atom probe tomography. We report on the evolution of the densely distributed MX (Ta(C, N)) and M2 X ((Cr, Ta)2 N) precipitates into blade-like and bulky Z-phase, respectively. The blade-like precipitates benefit from a smaller size compared to the bulky ones, providing precipitation hardening for creep resistance. We discuss an interactive role of carbon and nitrogen content in the formation of the Z-phase. Our findings pave the way towards designing new alloys with improved properties to serve in harsh environments at 650 °C. Graphical abstract: Highlights: Z-phase strengthened steels are potential material to build more efficient steam power plants. A fine distribution of Z-phase (TaCrN) precipitates is needed to provide long-term precipitation hardening in 12% Cr steels. Z-phase does not nucleate on its own, hence a full understanding of precursor phases to Z-phase and their evolution is vital. Atom Probe Tomography, Electron Microscopy, and X-ray Diffraction reveal the formation of Z-phase from different precursors. Ta(C, N) precipitates transform to a fine distribution of blade-like Z-phase precipitates. Nucleation and growth of Z-phase at (Cr, Ta)2 N precipitates result in unfavorable large Z-phase precipitates.